2020
DOI: 10.1021/acs.chemrestox.0c00154
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Biomarkers of DNA Damage and Mutagenicity in Mice Exposed to Acrylonitrile

Abstract: Acrylonitrile (ACN), which is a widely used industrial chemical, induces cancers in the mouse via unresolved mechanisms. For this report, complementary and previously described methods were used to assess in vivo genotoxicity and/or mutagenicity of ACN in several mouse models, including (i) female mice devoid of cytochrome P450 2E1 (CYP2E1), which yields the epoxide intermediate cyanoethylene oxide (CEO), (ii) male lacZ transgenic mice, and (iii) female (wild-type) B6C3F1 mice. Exposures of wild-type mice and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…A similar difference in relative sensitivity between the Hprt gene and lacI transgene was observed in Big Blue mice treated with another potent mutagen, N ‐ethyl‐ N 2 nitrosourea (ENU) (Walker et al, 1996), even though the average induced mutant frequencies (i.e., induced mutant frequency = treatment mutant frequency − background mutant frequency) in Hprt and lacI were similar. Additional studies demonstrated the ability to detect significant increases in mutations in the Hprt gene but not the lacI or lacZ genes following treatment of TGR mice with the cytotoxic chemotherapeutic cyclophosphamide (Walker et al, 1999), the direct‐acting alkylating agent ethylene oxide (Walker et al, 1997, 1999), and the epoxide‐forming industrial chemical acrylonitrile (Walker et al, 2020). One of the several possible reasons for these sensitivity differences is that the high baseline for background mutations in TGR mutation assays can make it difficult to resolve spontaneous and induced mutant frequencies and to demonstrate clearly the mutagenic effects of some test compounds in the transgene compared to the Hprt and Pig‐a genes with their relatively low background mutant frequencies (Walker et al, 2009).…”
Section: Concerns About the Potential Host Cell Mutagenicity Of Movmentioning
confidence: 99%
“…A similar difference in relative sensitivity between the Hprt gene and lacI transgene was observed in Big Blue mice treated with another potent mutagen, N ‐ethyl‐ N 2 nitrosourea (ENU) (Walker et al, 1996), even though the average induced mutant frequencies (i.e., induced mutant frequency = treatment mutant frequency − background mutant frequency) in Hprt and lacI were similar. Additional studies demonstrated the ability to detect significant increases in mutations in the Hprt gene but not the lacI or lacZ genes following treatment of TGR mice with the cytotoxic chemotherapeutic cyclophosphamide (Walker et al, 1999), the direct‐acting alkylating agent ethylene oxide (Walker et al, 1997, 1999), and the epoxide‐forming industrial chemical acrylonitrile (Walker et al, 2020). One of the several possible reasons for these sensitivity differences is that the high baseline for background mutations in TGR mutation assays can make it difficult to resolve spontaneous and induced mutant frequencies and to demonstrate clearly the mutagenic effects of some test compounds in the transgene compared to the Hprt and Pig‐a genes with their relatively low background mutant frequencies (Walker et al, 2009).…”
Section: Concerns About the Potential Host Cell Mutagenicity Of Movmentioning
confidence: 99%
“…+, positive; ±, either positive or negative in several assays; -, negative; Fischer 344 rat strain; HID, highest ineffective dose; LEF, lowest effective dose; N/T, not tested; - S9, without metabolic activation; + S9, with metabolic activation; Data from ECHA 2018 3 ; IARC 1999 2 ; Walker et al 2020a,b. 22,23 …”
Section: Resultsmentioning
confidence: 99%
“…+, positive; ±, either positive or negative in several assays; -, negative; HID, highest ineffective dose; Fischer 344 rat strain; LEF, lowest effective dose; SD, Sprague-Dawley rat strain; Data from ECHA 2018 3 ; IARC 1999 2 ; Walker et al 2020a,b. 22,23 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations